Population pharmacokinetics of modafinil acid and estimation of the metabolic conversion of modafinil into modafinil acid in 5 major ethnic groups of China - Wu Ke-hua; Guo Tao; Deng Chen-hui; Guan Zheng; Li Liang; Zhou Tian-yan; Lu Wei (Acta Pharmacologica Sinica; Vol 33, No 11 (November 2012): Acta Pharmacologica Sinica (Special Feature: Pharmacometrics), 2016)
Aim: To describe the population pharmacokinetic profile of modafinil acid and to compare the extent of metabolism of modafinil into modafinil acid in 5 major ethnic groups (Han, Mongolian, Korean, Uygur, and Hui) of China. Methods: In a multi-center, open-label, single dose clinical trial, 49 healthy volunteers from the 5 ethnic groups received 200 mg of modafinil orally. Blood samples for pharmacokinetic evaluation of modafinil and modafinil acid were drawn before and at different time after the administration. Systematic population pharmacokinetic (PopPK) modeling for modafinil acid was conducted, integrating with our previous PopPK model for modafinil. The influence of ethnicity, gender, height, body weight and body mass index (BMI) was estimated. The extent of metabolism of modafinil into modafinil acid, expressed as the relative conversion fraction, was estimated and compared among the 5 ethnic groups. Results: When combined with the PopPK model of modafinil, the concentration of modafinil acid versus time profile was best described with a one-compartment model. The typical clearance and volume of distribution for modafinil acid were 4.94 (l/h) and 2.73 (l), respectively. The Korean group had 25% higher clearance, and the Uygur and Hui groups had 12% higher clearance than the Han group. The median for the relative conversion fraction was 0.53 for Koreans, and 0.24 for the other 4 ethnicities. Conclusion: Ethnicity has significant influence on the clearance of modafinil acid. When patients in the 5 ethnic groups are administered drugs or prodrugs catalyzed by esterases and/or amidases, the variability in the extent of drug metabolism should be considered.